2020
DOI: 10.1097/jce.0000000000000378
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Speckle Noise and Image Enhancement in Ultrasound Image Using Filtering Technique and Edge Detection

Abstract: Ultrasound (US) imaging application in medicine and other fields is enormous. It has several advantages over other medical imaging modalities. The use of US in diagnosis is well established because of its noninvasive nature, portable, accurate, low-cost imaging modality, capable of forming real-time imaging and continuing improvement in image quality. Medical images and satellite images are usually degraded by noise during image acquisition and transmission process. It is estimated that 1 out of every form med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Functional study of changes in ultrasound images or Doppler ultrasound spectrum produced by the physiological characteristics of certain organs and tissues: echocardiography and Doppler ultrasound can be used to detect double power systolic and diastolic function, blood flow and blood flow measurement, gallbladder swelling and gastric function discharge, respiratory diaphragm activity, and so on [ 12 ]. Doppler ultrasound can be divided into pulse Doppler, continuous Doppler, high pulse repetition rate Doppler, multipoint gated Doppler, and color Doppler flow imaging.…”
Section: Ultrasound Imaging Researchmentioning
confidence: 99%
“…Functional study of changes in ultrasound images or Doppler ultrasound spectrum produced by the physiological characteristics of certain organs and tissues: echocardiography and Doppler ultrasound can be used to detect double power systolic and diastolic function, blood flow and blood flow measurement, gallbladder swelling and gastric function discharge, respiratory diaphragm activity, and so on [ 12 ]. Doppler ultrasound can be divided into pulse Doppler, continuous Doppler, high pulse repetition rate Doppler, multipoint gated Doppler, and color Doppler flow imaging.…”
Section: Ultrasound Imaging Researchmentioning
confidence: 99%
“…Mustafa et al carried out a comparative study on nine speckle reducing filters and five edge detection operators. 24 Authors found best results with linear neighborhood averaging and sobel edge detection. 24 It was observed that indeterminacy information in ultrasound images often gets overlooked in the traditional de-speckling methods.…”
Section: Introductionmentioning
confidence: 96%
“…24 Authors found best results with linear neighborhood averaging and sobel edge detection. 24 It was observed that indeterminacy information in ultrasound images often gets overlooked in the traditional de-speckling methods. This problem is mostly solved by using, fuzzy sets.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Edges are important features in images and provide prominent information about objects in the natural scenes, while edge strength is essential to computer vision, image processing, and pattern recognition, especially directly edge detection, contour detection, and image segmentation. Its applications benefit many fields, including image segmentation [1][2][3], object recognition [4], remote sensing [5,6], medical imaging [7][8][9], 3D reconstruction [10], face recognition [11,12], and image retrieval [11,13]. In the past several decades, various edge feature enhancement approaches have been proposed, including gradient-based methods [14][15][16], morphology gradient methods [17,18], logicbased methods [19], machine learning methods [2,20,21], local energy [22,23], and phase congruency [24,25].…”
Section: Introductionmentioning
confidence: 99%